MxB Disrupts Hepatitis C Virus NS5A–CypA Complex: Insights From a Combined Theoretical and Experimental Approach - Li, Quanjie; An, Ni; Yin, Xiao; Zhang, Ruixin; Shao, Huihan; Yi, Dongrong; Cen, Shan (Frontiers in Microbiology, 2022)
The human myxovirus resistance B (MxB) protein is an interferon-induced restriction factor that fights a wide range of viruses. We previously demonstrated that MxB binds to Hepatitis C virus (HCV)-encoded nonstructural protein 5A (NS5A) and inhibits HCV infection by impairing the formation of cyclophilin A(CypA)-NS5A complex. However, the molecular details about how the presence of MxB diminishes the binding of NS5A to CypA remain uncovered. In this study, through molecular dynamic simulations and biochemical assays, we characterized that MxB binds to NS5A domain I through its N-terminal and GTPase domains. Specifically, amino acids (aa.) 189–191 and aa. 330–334 within MxB, together with NS5A residues aa.71–73 are crucial for MxB-NS5A interaction. Furthermore, we predicted the CypA: NS5A and CypA: NS5A: MxB complexes and calculated the per-residue energy decomposition for identified key residues of CypA-NS5A interface. A 28% decrease in CypA-NS5A binding affinity was observed in the presence of MxB, suggesting a weakened CypA-NS5A association upon binding of MxB to NS5A, which may contribute to MxB mediated inhibitory effect on the formation of CypA-NS5A complex. This work provides information for the antiviral mechanism of MxB and may facilitate the discovery of new strategies to combat CypA-dependent viruses.